Three centuries of travel writing by Muslim women - Lambert-Hurley, Siobhan; Majchrowicz, Daniel; Sharma, Sunil, 1964- (Indiana University Press, 2022)
"When thinking of intrepid travelers from past centuries, we don't usually put Muslim women at the top of the list. And yet, the stunning firsthand accounts in this collection completely upend preconceived notions of who was exploring the world. Editors Siobhan Lambert-Hurley, Daniel Majchrowicz, and Sunil Sharma recover, translate, annotate, and provide historical and cultural context for the 17th- to 20th-century writings of Muslim women travelers in ten different languages. Queens and captives, pilgrims and provocateurs, these women are diverse. Their connection to Islam is wide-ranging as well, from the devout to those who distanced themselves from religion. What unites these adventurers is a concern for other women they encounter, their willingness to record their experiences, and the constant thoughts they cast homeward even as they traveled a world that was not always prepared to welcome them. Perfect for readers interested in gender, Islam, travel writing, and global history, Three Centuries of Travel Writing by Muslim Women provides invaluable insight into how these daring women experienced the world-in their own voices"--